2018
DOI: 10.1167/iovs.17-23183
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Density Is Associated With Retinal Ganglion Cell Axonal Volume in the Laminar Compartments of the Human Optic Nerve Head

Abstract: Microvascular density is closely coupled to RGC axonal volume in the ONH. The posterior laminar cribrosa is a site of high blood supply as evidenced by a greater ratio of microvascular density to RGC axonal volume. The greater percentage of tissue volume occupied by microvasculature in the prelaminar region may implicate it as a site where significant connections between the central retinal artery and short posterior ciliary arteries occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…3 Furthermore, a study utilizing a mathematical model suggested that the central area of the LC was more vulnerable to reduced blood supply following IOP elevation. 36 In addition, Kang et al 4 found that microvascular density correlates with retinal ganglion cell axonal volume in all regions of the ONH, but at a particularly greater ratio in the posterior LC, emphasizing the importance of this region for studies involving vascular parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Furthermore, a study utilizing a mathematical model suggested that the central area of the LC was more vulnerable to reduced blood supply following IOP elevation. 36 In addition, Kang et al 4 found that microvascular density correlates with retinal ganglion cell axonal volume in all regions of the ONH, but at a particularly greater ratio in the posterior LC, emphasizing the importance of this region for studies involving vascular parameters.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In particular, microvascular perfusion is vital for the health of the optic nerve axons. 3,4 Alterations in the ophthalmic vasculature due to changes in perfusion pressure, vascular tone, local resistance, and even systemic dysregulation have been shown to increase the risk of glaucoma. 58 In addition, pathology associated with the optic nerve vasculature, such as disc hemorrhages (DHs), can be an important indicator in the development and progression of glaucoma.…”
mentioning
confidence: 99%
“…In fact, the posterior lamina is implicated as the primary site of disruption in glaucoma, and emerging studies show a significant decrease in vessel density and blood flow in POAG in the deeper layers of the ONH compared with controls (Nascimento et al, 2019). Microvascular density correlates with RGC axon volume across all areas at the ONH, but the correlation is greater at the posterior lamina cribrosa, further emphasizing the importance of changes in vascular parameters at this site (Kang et al, 2018). Narrowing of retinal blood vessels is also characteristic of advanced glaucomatous optic nerve damage, indicating that vascular changes occur in the retina in addition to the site of injury at the ONH Rankin and Drance, 1996).…”
Section: Vascular Dysfunction In Glaucomamentioning
confidence: 98%
“… 69 Recently, confocal imaging of thick sections has been used to look at capillary and RGC axon density. 70 This method also lacks the ability to image the vasculature at multiple levels of IOP, but it has the benefit of being able to label capillaries and other tissues that the plastic cast method removes. Others have been able to investigate the effects of IOP on ONH vessel function in live rats through OCT-A.…”
Section: Discussionmentioning
confidence: 99%